2002
DOI: 10.1002/jmv.2198
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of human group C rotavirus infections in Argentina

Abstract: The incidence of human group C rotavirus infections among children and adults in Buenos Aires was evaluated by enzyme linked immunosorbent assays (ELISA) based on recombinant group C VP6 protein (Cowden strain). A total of 976 stool samples taken from patients (ages 6 months to 15 years) with acute diarrhea were tested for the presence of group C rotavirus. Among these, only 10 (1.02%) were group C rotavirus positive by enzyme-linked immunosorbent assay (ELISA) confirmed by absorption with group C VP6 antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
7
28
0
Order By: Relevance
“…The average detection rates of CV (10.4%), AstV (2.7%) and AdV 40/41 (1.4%) were comparable to those reported (14.0%, 3.0 % and 6.0%) in industrialized and non-industrialized countries [28 -33]. Otherwise, the RVC detection rate reported in Facatativá, was higher than those reported in Argentina (1.02 %) [34] and Japan (6.8 %) [35].…”
Section: Discussionsupporting
confidence: 52%
“…The average detection rates of CV (10.4%), AstV (2.7%) and AdV 40/41 (1.4%) were comparable to those reported (14.0%, 3.0 % and 6.0%) in industrialized and non-industrialized countries [28 -33]. Otherwise, the RVC detection rate reported in Facatativá, was higher than those reported in Argentina (1.02 %) [34] and Japan (6.8 %) [35].…”
Section: Discussionsupporting
confidence: 52%
“…An alternative hypothesis to explain the presence of animal-like strains in the communal sewage is that they might infect humans. The usually low detection rate of group C rotaviruses in childhood gastroenteritis (around 1% for children less than 5 years of age [3,5,41]) contrasts with reports of the relative abundance of antibodies against the virus in the same age group, as nearly 20% to 30% of children develop an antibody response to group C rotavirus by 5 years of age (14,21,37). An apparent increase in the serological prevalence of group C rotavirus has been observed among people of rural communities, an increase which has been linked to enhanced exposure to animals (13).…”
Section: Vol 74 2008 Group C Rotavirus In Communal Sewage 3397mentioning
confidence: 89%
“…In other countries serological surveys have suggested that group C rotavirus infections are far more common than actual virus identification may have indicated (2,7,13,19). These surveys, however, also included adults, among whom there was usually a higher level of group C rotavirus seropositivity than among infants and young children.…”
Section: Discussionmentioning
confidence: 99%